Atterberg limits are not appropriate for peat soils - O'Kelly, Brendan (My University, 2015)
This paper reports on the challenges associated with the determination of the Atterberg limits for peat, fundamental issues regarding the appropriateness of Atterberg limit concepts applied to peat and peaty soils and their use in characterising the engineering behaviour of these materials. As demonstrated in the present study, different sample preparation methods and preloading of the peat material (which gives the organic solids some stress history because of their compressible nature) can result in significantly different Atterberg limit values being measured. The significance of reinforcement and scale effects related to the peat fibres for the thread-rolling method is investigated. It is concluded that the Atterberg limit tests are not appropriate for peat in that the deduced plastic range for the peat test material is notional and the calculated liquidity index values are not reliable indicators of its consistency. In assessing the likely engineering behaviour of peat material, a more useful suite of index tests is its natural water content, organic content, fibre content and degree of humification
PUBLISHED
Keywords: Smart & Sustainable Planet; Environmental Geotechnics; FIBRE; GEOTECHNICAL ENGINEERING; Geotechnics; PEAT; PEAT SOILS